The Role Of Entrepreneurial Motivation And Social Network Relationship On Business Performance Of Herbal Medicine Sellers - Dwi Hastuti; Fitri Wulandari (Relevance: Journal of Management and Business, 2021)
The purpose of this study is to analyze the effect of entrepreneurial motivation and social network relationship on the business performance of herbal medicine sellers. The object of this research was the sellers of herbal drink/the peddler of biopharmaca/herbal medicine store in Banyu Urip Surabaya and surrounding areas. The sampling technique used purposive sampling technique with a total sample of 91 respondents. The data analysis method applied regression analysis with the help of IBM SPSS software version 21. The results indicate that there is a positive and significant influence of entrepreneurial motivation on the business performance of herbal medicine sellers. However, social network relationships have a positive and insignificant effect on improving the business performance of herbal medicine sellers. This research provides the strong motivation for entrepreneurs to improve their business performance becoming autonomy and independence. This means that the desire to work independently, to develop their own business, and to have financial independence are the strongest impetus for them to be successful in business indicated by better financial performance.